2021
DOI: 10.3389/fpsyg.2021.661235
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Level Evaluation Method Based on a Deep Neural Network for Online Learning: From a Bloom’s Taxonomy of Cognition Objectives Perspective

Abstract: The evaluation of the learning process is an effective way to realize personalized online learning. Real-time evaluation of learners’ cognitive level during online learning helps to monitor learners’ cognitive state and adjust learning strategies to improve the quality of online learning. However, most of the existing cognitive level evaluation methods use manual coding or traditional machine learning methods, which are time-consuming and laborious. They cannot fully mine the implicit cognitive semantic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The most significant feature of MOOCs is the two-way flow of information as compared to the traditional teaching methods available in literature. It is due to the fact that in the MOOC teaching method, students can discuss the difficulties they have encountered in their own learning or the areas of the teaching that they do not understand [ 9 , 10 ]. The problems or issues are conveyed to the teacher in the form of a message, and the teacher can understand the students' learning situation.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant feature of MOOCs is the two-way flow of information as compared to the traditional teaching methods available in literature. It is due to the fact that in the MOOC teaching method, students can discuss the difficulties they have encountered in their own learning or the areas of the teaching that they do not understand [ 9 , 10 ]. The problems or issues are conveyed to the teacher in the form of a message, and the teacher can understand the students' learning situation.…”
Section: Introductionmentioning
confidence: 99%
“…Language models can also play a role in evaluating and scoring student responses to assessment material (Cheng et al., 2021; Cotton et al., 2023; Lee, 2023). However, the focus is on ‘play a role’ rather than the whole role (Cotton et al., 2023; Rahm & Rahm‐Skågeby, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Educators, among other uses such as exercises and classroom discussions, can use language models to generate teaching and assessment material (Dhruv et al., 2018; Roy & Rambo‐Hernandez, 2021). Language models such as ChatGPT and Perplexity AI can contribute to student learning and achievement through personalised learning strategies, teaching interventions, and recommended resources (Cheng et al., 2021; Farrokhnia et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Linking the learned concepts with the concepts of daily life inside and outside the school. Extensive reading of vocabulary outside the textbook [26,27]. Several studies indicated that educational games develop this strategy and through it academic achievement can be predicted.…”
Section: Deep Learning Strategymentioning
confidence: 99%